STUDI KOMPARATIF VARIASI LAPISAN ELEKTRODA RD -260 E 6013 TERHADAP UJI MEKANIK BAJA A36 PADA PENGELASAN BAWAH AIR - ALA Risdianto; RP Ulmi; IA Kuniallah; AR Okvitasari (Bajang Institute, 2024)
Underwater welding has advantages, one of which is that it allows the joining of materials at sea depth quickly, efficiently, and saves repair costs. In underwater work using the type of electrode used underwater (underwater welding) is a special electrode which in terms of price is much more expensive than conventional electrodes in general. In this research, a problem is raised that will discuss how the difference in E6013 electrode coatings commonly used for welding on land with welding in water. Based on the visual test results, electrodes with hot melt adhesive (PLP) coating show more defects than electrodes with resin coating, this is because during the welding process in water the flame of the hot melt adhesive (PLP) coating is less stable. The results of the breaking test obtained an average peak load value from welding on land of 68957 Fm which is used as a reference in determining the type of electrode coating variation that is good. The average peak load value of the electrode with resin coating showedvalue which is close to the average peak load value of welding on land which is 52161 Fm.